Manipulation of Transaction Value to Reduce Fees for Acquisition of Land and Building Rights - Suhaimi Suhaimi (Universitas Syiah Kuala, 2021)
The purpose of this study is to analyze the responsibility of taxpayers who manipulate transaction values in order to reduce Fees for Acquisition of Land and Building Rights (BPHTB). This research is inspired by the results of previous research that many BPHTB taxpayers manipulate transaction values to reduce BPHTB, but they are missed from legal responsibility, so that their actions seem normal in society and are not perceived as despicable and violating of the law. This research is a normative legal research using a statutory approach, so that it can be seen how the responsibility of taxpayers who are not honest in paying BPHTB. The results showed that in statutory regulations cannot be found administrative sanctions imposed on taxpayers who manipulated transaction values to reduce BPHTB. In fact taxpayer's actions are really detrimental regional finance, because their taxes are paid to the Regional Treasury as the original financial resources. Sanctions contained in statutory regulations are only criminal sanctions, as regulated in Article 174 of Law Number 28 of 2009 with the threat of imprisonment for a maximum of one year if due to negligence and a maximum of two years if done intentionally.